2010
DOI: 10.1111/j.1601-5223.1938.tb03219.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomenzahlen Finnlän-Discher Lepidopteren

Abstract: ZUSAMMENFASSUNG Es wurde die Chromosomenzahl 67 finnlandischer Tagschmetterlinge in den Reifeteilungen festgestellt, bei der Mehrzahl in beiden Geschlechtern, bei den ubrigen nur in dem einen. (Siehe Tabelle 1.) Die Chromosomenzahl schwankt zwischen 11 und 32; 58 % der Arten haben 29—31 Chromosomen. (Siehe Diagramm II.) Es ist auffallend, dass in funf Familien eine Art mit einer stark verminderten Chromosomenzahl vorkommt. Die bedeutende Grosse dieser Chromosomen lasst auf Sammelchromosomen schliessen, die ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 11 publications
4
20
1
Order By: Relevance
“…The final assembly of the nuclear genome comprises 49,851 contigs (N50=13 kb) and 8,262 scaffolds (N50=119 kb), with an overall coverage of 95 × (Supplementary Figs 4–6; Supplementary Tables 1 and 3). A linkage map based on 40,718 single nucleotide polymorphisms (SNPs)26 assigned 3,507 scaffolds (318 Mb) to 31 linkage groups, matching the 31 chromosomes reported for this species in a cytogenetic study28 (Supplementary Table 6; Supplementary Note 5). For subsequent superscaffolding, we applied an in-house method utilizing the linkage map, long MP data and PacBio reads.…”
Section: Resultsmentioning
confidence: 80%
“…The final assembly of the nuclear genome comprises 49,851 contigs (N50=13 kb) and 8,262 scaffolds (N50=119 kb), with an overall coverage of 95 × (Supplementary Figs 4–6; Supplementary Tables 1 and 3). A linkage map based on 40,718 single nucleotide polymorphisms (SNPs)26 assigned 3,507 scaffolds (318 Mb) to 31 linkage groups, matching the 31 chromosomes reported for this species in a cytogenetic study28 (Supplementary Table 6; Supplementary Note 5). For subsequent superscaffolding, we applied an in-house method utilizing the linkage map, long MP data and PacBio reads.…”
Section: Resultsmentioning
confidence: 80%
“…The name Ochlodes venatus was long used for the Ochlodes species of Europe, but it actually refers to its Far Eastern sister species, and the European taxon is now called Ochlodes sylvanus (Esper, 1777) ( ICZN 2000 ). Both European and Far Eastern species have the same chromosome number n=29 ( Federley 1938 , Lorković 1941 , Abe et al 2006 ), not n=13 as indicated by Bigger (1960) . Thus, the species name used by Bigger (1960) was probably misidentification.…”
Section: Resultsmentioning
confidence: 99%
“…The representatives of basal clades (see phylogeny in Leneveu et al 2009), the taxa of Melitaea cinxia (Linnaeus, 1758), Melitaea diamina (Lang, 1989), Melitaea athalia (Rottemburg, 1775), Melitaea trivia ([Denis & Schiffermüller], 1775) and Melitaea phoebe ([Denis & Schiffermüller], 1775) species groups demonstrate n=30-31 (Federley 1938, de Lesse 1960, Robinson 1971, Larsen 1975, Hesselbarth et al 1995). These haploid numbers are modal ones not only for Melitaea , but also for the family Nymphalidae and for the order Lepidoptera in whole (Robinson 1971, Lukhtanov 2000, 2014).…”
Section: Discussionmentioning
confidence: 99%